Isolation and immortalization of macrophages derived from fetal porcine small intestine and their susceptibility to porcine viral pathogen infections - Takenouchi, Takato; Masujin, Kentaro; Miyazaki, Ayako; Suzuki, Shunichi; Takagi, Michihiro; Kokuho, Takehiro; Uenishi, Hirohide (Frontiers in Veterinary Science, 2022)
Macrophages are a heterogeneous population of cells that are present in all vertebrate tissues. They play a key role in the innate immune system, and thus, in vitro cultures of macrophages provide a valuable model for exploring their tissue-specific functions and interactions with pathogens. Porcine macrophage cultures are often used for the identification and characterization of porcine viral pathogens. Recently, we have developed a simple and efficient method for isolating primary macrophages from the kidneys and livers of swine. Here, we applied this protocol to fetal porcine intestinal tissues and demonstrated that porcine intestinal macrophages (PIM) can be isolated from mixed primary cultures of porcine small intestine-derived cells. Since the proliferative capacity of primary PIM is limited, we attempted to immortalize them by transferring the SV40 large T antigen and porcine telomerase reverse transcriptase genes using lentiviral vectors. Consequently, immortalized PIM (IPIM) were successfully generated and confirmed to retain various features of primary PIM. We further revealed that IPIM are susceptible to infection by the African swine fever virus and the porcine reproductive and respiratory syndrome virus and support their replication. These findings suggest that the IPIM cell line is a useful tool for developing in vitro models that mimic the intestinal mucosal microenvironments of swine, and for studying the interactions between porcine pathogens and host immune cells.